Learning from online learning journals (OLJs): experiences of postgraduate students - Bavli, Bunyamin (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2023)
This study aims to explore the experiences of postgraduate students, Master's and Doctoral, on using online learning journals (OLJs). In line with the nature of the study, instrumental case study was managed by the researcher as a qualitative research design in the current study. Participants include 12 graduate students, Master's and Doctoral, studying Curriculum and Instruction. The researcher administered criterion sampling, which is one of the purposeful sampling methods, to determine participants. During the data collection process, the researcher employed interviews and written documents. Semi-structured in-depth interviews and a focus group interview were held with the participants within the scope of the interview. In respect to written documents, learning journals were reviewed by the researcher. Content analysis method, which is mostly adopted for written and visual data in qualitative research, was administrated to analyse the obtained data. The results suggest that keeping regular OLJs contributed to learners emotionally, cognitively and academically.
Keywords: Online learning journals; postgraduate education; postgraduate students; case study; experience; REFLECTIVE THINKING; PERCEPTIONS; OUTCOMES; QUALITY; Education & Educational Research